High incidence of candidaemia in a nationwide cohort: Underlying diseases, risk factors and mortality. (November 2018) - Lausch, K.R.; Søgaard, M.; Rosenvinge, F.S.; Johansen, H.K.; Boysen, T.; Røder, B.; Mortensen, K.L.; Nielsen, L.; Lemming, L.; Olesen, B.; Leitz, C.; Kristensen, L.; et al.
Abstract: Background: Denmark has a high incidence rate of candidaemia. A Nordic study suggested a higher Danish prevalence of haematological malignancies as an underlying reason. This nationwide study ascertained clinical characteristics of Danish candidaemia patients and investigated potential factors contributing to the high incidence and mortality. Methods: Microbiological and clinical data for candidaemia patients in 2010-2011 were retrieved. 30-day mortality was estimated by hazard ratios (HR) with 95% confidence intervals (CI, Cox regression). Results: Data were available for 912/973 candidaemia episodes (93.7%). Intensive care unit (ICU) held the largest share of patients (43.2%). Prevalent host factors were multi-morbidity (≥2 underlying diseases, 74.2%) and gastrointestinal disease (52.5%). Haematological disease was infrequent (7.8%). Risk factors included antibiotic exposure (90.5%), CVC (71.9%) and Candida colonisation (66.7%). 30-day mortality was 43.4%, and 53.6% in ICU. Mortality was lower for patients with recent abdominal surgery (HR 0.70, 95% CI: 0.54-0.92). Conclusion: A substantial prevalence of multi-morbidity and a high 30-day mortality was found. We hypothesise, that an increasing population of severely ill patients with prolonged supportive treatment and microbiological testing may in part explain the high candidaemia incidence in Denmark. Nationwide studies are warranted to clarify this issue.